Densidade calórica de cascudo-chinelo Loricariichthys platymetopon na planície alagável do alto rio Paraná. - Garcia, Daniela Aparecida (2008)
In this study was compared the muscular energy content of L. platymetopon in different sites of the upper Paraná river floodplain, and were inquired the potential relations of this content with environmental variables (water temperature, oxygen dissolved in the water, food availability, numerical relative abundance) and biological variables (size body and reproductive cycle). Quarterly collections, from September 2006 to June 2007, in lagoons and rivers, resulted in the sampling of 739 specimens, whose muscular caloric density was determined through calorimetric bomb. Differences between the caloric mean of males and females, and stages of gonadal development, had not been significant. The caloric density varied spatial and seasonally, being verified two trends of seasonal variation. The intensity of the correlation between caloric density and each environmental variable, as well as, the correlation form, varied with the site. The body size and the reproductive cycle had not been correlated to the caloric density.